Internalisasi Nilai Keislaman dan Nilai Pancasila dalam Membentuk Karakter Anak di Kampung Qur’an Desa Karang Sekaran Lamongan - Miftah, Zaini; Nisa', Ida Fauziatun (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2024)
This article conducts a study on the internalization of Islamic values and Pancasila values in shaping children's character with the main purpose of finding out the internalization strategy of values carried out in Qur'an villages, as well as to find out the supporting and inhibiting factors for the internalization of these values. The preparation of this article uses a qualitative approach with the type of case study research through qualitative descriptive analysis. Furthermore, the results of this article state that the strategy of internalizing Islamic values and Pancasila values in shaping children's character can be seen from four religious dimensions which include the credial aspect (creed), ritual aspect (worship), moral aspect (morals), and social aspects (mu'amalah). Meanwhile, the character value of Pancasila is seen from five, aspects that include: discipline, independence, democracy, nationalism, and social concern. The strategy of internalizing Islamic values and Pancasila values is carried out through moral acting, moral knowing, moral feeling and loving, and role modeling/uswah hasanah. Meanwhile, the supporting factor in this activity is the awareness and support from the law, institutions, related agencies, the environment, and the community. Meanwhile, the inhibiting factors are related to the Indonesian education system which does not pay attention to moral and ethical learning, a less supportive environment for children; lack of maximum socialization; and the lack of role of religious education in the formation of adolescent attitudes